2018
DOI: 10.1002/elps.201700413
|View full text |Cite
|
Sign up to set email alerts
|

Top‐down and bottom‐up characterization of nitrated birch pollen allergen Bet v 1a with CZE hyphenated to an Orbitrap mass spectrometer

Abstract: Tyrosine (Tyr) residues of the major pollen allergen of birch Betula verrucosa, Bet v 1a, were nitrated by peroxynitrite. This modification enhances the allergenicity. Modified tyrosines were identified by analyzing intact allergen variants in combination with top‐down and bottom‐up approaches. Therefore, a laboratory‐built sheath‐liquid assisted ESI interface was applied for hyphenation of CE to an Orbitrap mass spectrometer to localize individual nitration sites. The major focus was on identification of prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Gusenkov et al. demonstrated the potential of combining a top‐down and a bottom‐up strategy in a complementary manner . The birch pollen allergen Bet v 1a was nitrated with peroxynitrite which resulted in the formation of nitrotyrosine residues, known to be responsible for an enhanced allergenicity.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Gusenkov et al. demonstrated the potential of combining a top‐down and a bottom‐up strategy in a complementary manner . The birch pollen allergen Bet v 1a was nitrated with peroxynitrite which resulted in the formation of nitrotyrosine residues, known to be responsible for an enhanced allergenicity.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Y5 and Y120 nitration could not be detected and Y66 nitration was only found for ONOO -modified Bet v 1, but could not be quantified. Gusenkov and Stutz ( 60 ) later found that the reaction with ONOO leads to nitration of six tyrosine residues (Y5, Y66, Y81, Y83, Y150, Y158) with preferential nitration of the two surface-exposed tyrosine residues Y5 and Y66.…”
Section: Tyrosine Nitrationmentioning
confidence: 99%
“…Both bottom-up peptide mapping and top-down proteomic approach have been applied for detailed characterization of nitrated birch pollen allergen Bet v 1a by CZE coupled to an Orbitrap MS detector using a home-made low-sheath-flow CZE-ESI interface [267]. The bottom-up peptide mapping approach with tryptic digest made possible the unambiguous localization of nitration sites on the particular Tyr residues.…”
Section: Bottom-up Proteomics and Peptidomicsmentioning
confidence: 99%